2014
DOI: 10.1007/s10561-014-9463-8
|View full text |Cite|
|
Sign up to set email alerts
|

Defined serum- and xeno-free cryopreservation of mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) have vast potential in cell therapy, and are experimentally used in the clinic. Therefore, it is critical to find a serum- and xeno-free cryopreservation method. The aim of this study was to compare two serum- and xeno-free cryoprotectants for MSCs. Adipose tissue MSCs (Ad-MSCs) and bone marrow MSCs (BM-MSCs) were cryopreserved in two cryoprotectants: the defined serum- and xeno-free STEM-CELLBANKER™ (CB) and 10 % dimethyl sulfoxide (DMSO) in a xeno-free serum replacement cell cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 139 publications
0
19
0
Order By: Relevance
“…3,33,34 In contrast, other studies 10,[35][36][37] have demonstrated that cryopreserved MSC exhibit equivalent viability and immunosuppressive potential to freshly isolated MSC from cell culture. Consistent with these findings, we found that freeze-thawed MEP displayed a viability of 95% and retained the ability to effectively suppress lymphocyte proliferation in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…3,33,34 In contrast, other studies 10,[35][36][37] have demonstrated that cryopreserved MSC exhibit equivalent viability and immunosuppressive potential to freshly isolated MSC from cell culture. Consistent with these findings, we found that freeze-thawed MEP displayed a viability of 95% and retained the ability to effectively suppress lymphocyte proliferation in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…The list of commercially available chemically defined, protein-free, xeno-free and serum-free is constantly increasing [29] as discussed in recent reviews [30,31].…”
Section: Stem Cell Mediamentioning
confidence: 99%
“…To improve outcome of cryopreservation, the authors suggested nucleation temperature control during the freezing process [108]. Another recent report described the formulation of hMSCs using the FDA-approved commercial serum-free and xeno-free CPA known as STEM-CELLBANKER™ (Amsbio, UK) [29]. The cell viability was >90% (better than DMSO) and no morphological differences were observed, but cell growth was slower.…”
Section: Formulation and Storage Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 To assess the osteogenic potential of cryopreserved MSCs, the presence of calcium deposition after osteogenic induction of cryopreserved MSCs was confirmed by Alizarin Red or Von Kossa staining. 10,13,51,53,54 These osteogenic-like cells showed a high expression level of osteogenic markers such as osteocalcin (OSC) and alkaline phosphatase (ALP). 51,54 The presence of proteoglycan after chondrogenic induction of cryopreserved MSCs was confirmed by Alcian Blue or Safranin O staining.…”
Section: Cell Differentiation Capacitymentioning
confidence: 99%